Vision-Based Fall Risk Assessment Through Attention Augmented Neural Encoding and Data Augmentation - Chunhua Pan; Rui Miao; Qing Zhang; Boting Qu; Xin Wang (IEEE Access)
Falls among elderly individuals and other at-risk populations represent a significant public health concern, underscoring the need for proactive and accessible fall risk assessment methods. Although prior systems using wearable sensors or depth cameras have demonstrated potential, their widespread adoption is often constrained by user discomfort, setup complexity, and the high cost of specialized equipment such as Kinect. To address these limitations, we propose GTAE-FRA, a novel vision-based deep learning framework for fall risk assessment that leverages standard, widely available RGB cameras to record Five times Sit-To-Stand (FSTS) test videos. GTAE-FRA begins with a robust video processing pipeline that includes 3D pose estimation, noise filtering, and Dynamic Time Warping (DTW)-based matching to extract reliable Body Skeleton Key Point (BSKP) sequences. These sequences are then fed into GTrans, an attention-augmented encoder combining message passing aggregation mechanism with Transformer-based spatial-temporal modeling for nuanced feature extraction. To overcome limited data availability, six skeleton-oriented data augmentation strategies are applied, which significantly enhance the diversity and robustness of training samples. Experimental results on a dataset of 450 FSTS videos demonstrate the effectiveness of GTAE-FRA, achieving impressive performance with detection accuracy, weighted F1 score, macro F1 score, and AUC of 87.00%, 87.01%, 88.92%, and 97.96%, respectively. These results represent average improvements of 2.49%, 2.66%, 2.24% and 1.78% over baseline methods across the respective metrics.